“Making It Worse than What Really Happened”: Social Chaos and Preparedness as Problematic Mythologies in Disaster Communication - Baker, Natalie D. (Frontiers in Communication, 2016)
This perspective piece explores both social chaos and disaster preparedness as mythologies that are a persistent part of problems with disaster communication. It argues that while extant scholarship acknowledges disaster myths that advance the belief that social chaos and, for example, looting is common is problematic, there has not been much done to mitigate this in practice. Furthermore, the continued focus on social disorder in institutional efforts does not recognize inherent skills and capabilities of citizens both at risk for and affected by disaster. Here I argue, the concept of preparedness is an expectation that dichotomizes human behavior and is a form of social control. Those who are not prepared according to institutional norms have the potential to be unruly. The management of large emergencies must mitigate myths and advance more accurate understandings of pro-sociality in disasters. To this end, the status quo communicates bad information about human behavior in crisis that perpetuates a paternalistic institutional approach that stagnates equitable disaster management. Here, I pose a call for new directions in disaster research given such issues.